Architextual authenticity : constructing literature and literary identity in the French Caribbean - Herbeck, Jason (Contemporary French and francophone cultures, 2017)
Taking as its point of focus diverse canonical and lesser-known texts from Guadeloupe, Martinique and Haiti published between 1958 and 2013, this text examines the trope of the house (architecture) and the meta-textual construction of texts (architexture) as a means of conceptualizing and articulating how authentic means of expression are and have been created in French-Caribbean literature over the greater part of the past half-century-whether it be in the context of the years leading up to or following the departmentalization of France's overseas colonies in the 1940's, the wrath of Hurricane Hugo in 1989, or the devastating Haiti earthquake of 2010.